Pemanfaatan Akun Belajar.Id Untuk Meningkatkan Kualitas Pembelajaran IPS Di SMP Negeri 03 Bengkulu Tengah - Yuningsih, Yuningsih; somantri, Manap; Sumarsih (Manajer Pendididikan, 2025)
This study to analyze the utilization of Belajar.id accounts in enhancing the quality of Social Studies learning at SMP Negeri 03 Bengkulu Tengah. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The results indicate that the optimal use of Belajar.id accounts significantly improves Social Studies teachers' access to various digital learning resources, strengthens digital learning interactions, and enhances teachers' creativity in designing interactive teaching materials. The novelty of this research lies in the development of practical strategies for utilizing Belajar.id accounts to support Social Studies learning processes at the junior high school level. This study provides practical recommendations for school administrators and Social Studies teachers to optimize the use of Belajar.id accounts in order to improve learning quality in the digital era.